The Determinants Of Purchase Intention For Subtle Luxury Fashion Goods Among Malaysian Consumers - Ting, Mao Seng (2021)
The global sales of luxury fashion products have dropped significantly due to the COVID 19 outbreak, and many experts foresee that the sales of the luxury market will continue to decline in 2021, coupled with the decline need of signaling wealth for conspicuous luxury goods. The two factors have contributed to the rise of inconspicuous luxury fashion goods consumption. Therefore, this study examines the factors that influence Malaysian consumers’ inconspicuous consumption or purchase intention of subtle luxury fashion goods. This study contributes to the existing body of knowledge by integrating both Theory of Interpersonal Behaviour (TIB) and Model Action Phase (MAP) as underlying theories. This study also contributes to a growing body of literature on luxury fashion goods' purchase intention by empirically examining the attitudinal, social, and affective factors. There have been very few past research that examined all three simultaneous factors that influence consumers’ purchase intention of luxury fashion goods. Furthermore, this research investigates the contextual factors and habits to explain the variance between purchase intentions and inconspicuous consumption behaviours. Apart from the theoretical contributions mentioned, this study suggests that luxury marketers, luxury owners, and luxury retailers should implement limited-edition and personalisation strategy to enhance product exclusivity, improve consumers’ awareness of the subtle luxury fashion items through endorsement strategy, create a promotion video that emphasises their subtle luxury fashion product quality, engage with customers by profiling their shopping history and collecting customer information, create heightened store atmospherics for inconspicuous consumers, and involve various corporate social responsibility campaigns